Kemampuan Dinding Kaca dalam Mentransferkan Intensitas Cahaya yang Melewati Dinding Kaca - Taufiq Taufiq; Ahmad Syuhada; Hamdani Hamdani (Jurnal Teknik Mesin Unsyiah, 2014)
The sun transfers heat energy to the earth with radiation mode. To reach the air temperature with thermal comfort in the indoor air temperature then need to re-view using AC, but if the energy intensity of the sun's too much that goes into the conditioning room through a glass wall that will cause the AC is too big. This will lead to the use of electrical energy is too wasteful. To minimize the AC in the room caused by a number of incoming solar radiation intensity of heat is done by using a glass inhibitory properties of low light intensity. The purpose of this study was to determine the extent of the inhibitory effect of light intensity into the room by each type of glass. The research was done by varying the type of glass that will be mounted on the solar collector, rain glass, blue glass, black glass, One way glass, glass orange. Measurement of light intensity and temperature data were taken every 30 minutes within a period of 3 hours. Based on the results of the study five types of glass is the importance of the election of the best level of inhibition glass is types of glass One way because the light intensity 400 W/m2 - 500 W/m2, resulting in room temperature is 45 0C.